Secretion of adipokines by human adipose tissue in vivo: Partitioning between capillary and lymphatic transport - Miller, N; Charles Michel, C; Nazeem Nanjee, M; Olszewski, W; Miller, I; Hazell, M; Olivecrona, G; Sutton, P; Humphreys, S; Frayn, K (2011)
Peptides secreted by adipose tissue (adipokines) may enter blood via capillaries or lymph. The relative importance of these pathways for a given adipokine might influence its biological effects. Because this has not been studied in any species, we measured the concentrations of seven adipokines and eight nonsecreted proteins in afferent peripheral lymph and venous plasma from 12 healthy men. Data for nonsecreted proteins were used to derive indices of microvascular permeability, which in conjunction with the molecular radii of the adipokines were used to estimate the amounts leaving the tissue via capillaries. Transport rates via lymph were estimated from the lymph adipokine concentrations and lymph flow rates and total transport (secretion) as the sum of this and capillary transport. Concentrations of nonsecreted proteins were always lower in lymph than in plasma. With the exception of adiponectin, adipokine concentrations were always higher in lymph (P < 0.01). Leptin and MCP-1 were secreted at the highest rates (means: 43 μg/h or 2.7 nmol/h and 32 μg/h or 2.4 nmol/h, respectively). IL-6 and MCP-1 secretion rates varied greatly between subjects. The proportion of an adipokine transported via lymph was directly related to its molecular radius (r s=+0.94, P = 0.025, n = 6), increasing from 14 to 100% as the radius increased from 1.18 (IL-8) to 3.24 nm (TNFα). We conclude that the lymph/capillary partitioning of adipokines is a function of molecular size, which may affect both their regional and systemic effects in vivo. This finding may have implications for the physiology of peptides secreted by other tissues. © 2011 the American Physiological Society.